ANALISIS FINANSIAL USAHA PERIKANAN TANGKAP BELAT DI KOTA BONTANG (Financial Analysis of Set Net Fisheries Business in Bontang City) - KAMILAN, KAMILAN; SYAHRIR, M; SUSILO, HERU (Universitas Mulawarman (University of Mulawarman), 2024)
Indonesian capture fisheries have a responsibility as a source of economic growth, a provider of animal protein food and a source of employment. Bontang City is one of the cities in East Kalimantan with good potential for capture fisheries, from a variety of capture fisheries activities, one of the most widely used fishing gear is the splint. The purpose of this research is to discuss the financial analysis of mullet fishing business. This research uses a sampling method, namely purposive sampling with 30 fishermen respondents who use splint fishing gear in Bontang City. The analysis methods used are NPV, Net B/C, IRR, and Payback Period. The results obtained based on the analysis of the splint fishing business are feasible to continue, when viewed based on the NPV investment criteria, IRR, Net B / C Ratio, Payback Period. The NPV value obtained is Rp.42,119,332, IRR of 87%, Net B / C Ratio of 4.17 and payback period for 1 year 2 months